IgG4-associated hypophysitis coexisting with MALT lymphoma and gangliocytoma: first case report and literature review - Zou, Dongbo; Jiang, Li; Yang, Tao; Cheng, Jingmin; Ma, Yuan (Frontiers in Neurology, 2023)
IgG4-related or IgG4-associated hypophysitis is a rare disease characterized by the infiltration of IgG4-positive plasma cells into pituitary gland tissue. Gangliocytomas in the sellar region are also extremely rare and are associated with pituitary adenomas in the majority of cases. Sellar mucosa-associated lymphoid tissue (MALT) lymphoma is an exceedingly rare condition. In this study, we present a case of IgG4-associated hypophysitis coexisting with MALT lymphoma and gangliocytoma. However, to elucidate the potential pathophysiological relationship, it is imperative to gather additional cases of IgG4-related hypophysitis accompanied by MALT lymphoma and gangliocytoma.